Junior university: fostering young minds’ interest in higher education - Silva, Vítor; Urbano, Diana; Pinto, Isabel Macedo; Ribeiro da Silva, Maria D. M. C.; Graça, Pedro; Soares, Susana; Almeida, Teresa (Frontiers in Education, 2024)
The Universidade Júnior (U.Jr.) program, initiated by the University of Porto (U.Porto), Portugal, is a comprehensive educational initiative conducted during the summer months, primarily targeting the 10–18 age group. The program aims to promote science, technology, arts, humanities, and sports knowledge among elementary and secondary-level students and to influence their vocational choices and higher education aspirations. The study analyses the relationship between participation in the U.Jr. program and subsequent enrollment in higher education at U.Porto. It utilises data collected from 2006 to 2022, comparing U.Jr. participants with students who enrolled as freshmen at U.Porto. A Pearson correlation coefficient was applied to establish the connection between these datasets. Data analysis reveals a significant positive relationship between participation in U.Jr. and the choice of U.Porto for higher education. The study shows that 22 out of 100 first-year students at U.Porto in 2021 had previously attended U.Jr. Moreover, the geographical provenance of participants and U.Porto first-year students showed a robust correlation. The findings suggest that U.Jr. has a substantial impact on attracting students to U.Porto and influencing their academic choices. The program’s diverse activities, coupled with its inclusive approach, have been instrumental in increasing the university’s attractiveness and helping mitigate the country’s low higher education rates. The study underscores the importance of such initiatives in shaping students’ educational trajectories and choices for higher education.